2020
DOI: 10.3390/md18080430
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Peptides from Swim Bladders of Giant Croaker (Nibea japonica) and Their Protective Effects against H2O2-Induced Oxidative Damage toward Human Umbilical Vein Endothelial Cells

Abstract: Five different proteases were used to hydrolyze the swim bladders of Nibea japonica and the hydrolysate treated by neutrase (collagen peptide named SNNHs) showed the highest DPPH radical scavenging activity. The extraction process of SNNHs was optimized by response surface methodology, and the optimal conditions were as follows: a temperature of 47.2 °C, a pH of 7.3 and an enzyme concentration of 1100 U/g, which resulted in the maximum DPPH clearance rate of 95.44%. Peptides with a Mw of less than 1 kDa (SNNH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
(50 reference statements)
5
22
0
Order By: Relevance
“…These findings suggest that the peptides from hydrolysate of monkfish muscle could strongly protect H 2 O 2 -induced oxidative damage HepG2 cells, especially at high concentrations. These results were consistent with the data presented by Zheng et al [ 59 ], who showed that hydrolysate of swim bladders of Nibea japonica exposed to human umbilical vein endothelial (HUVECs) cells during 24 h did not decrease cell viability. Indeed, a collagen peptide of the swim bladders, named SNNH-1, promoted the growth of these cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings suggest that the peptides from hydrolysate of monkfish muscle could strongly protect H 2 O 2 -induced oxidative damage HepG2 cells, especially at high concentrations. These results were consistent with the data presented by Zheng et al [ 59 ], who showed that hydrolysate of swim bladders of Nibea japonica exposed to human umbilical vein endothelial (HUVECs) cells during 24 h did not decrease cell viability. Indeed, a collagen peptide of the swim bladders, named SNNH-1, promoted the growth of these cells.…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in intracellular ROS levels using a pretreatment with these hydrolysates suggested that sequestration or neutralization of free radicals is a possible mechanism of action in the antioxidant peptides found in hydrolysates. Similar results were obtained by Zhen et al [ 59 ] who studied the effect of SNNH-1 on ROS levels in HUVECs cells. After H 2 O 2 treatment, the fluorescence intensity in HUVECs cells was significantly higher compared to the control.…”
Section: Discussionsupporting
confidence: 90%
“…The hydrophobic nature of peptides helps elevate their antioxidant properties. They increase the interaction with lipid targets by virtue of hydrophobic associations or peptide entry into target organs, which are conducive to the realization of antioxidant effects [26,27]. Some studies have shown that negatively charged amino acids (NCAAS), such as glutamic and aspartic acids, exhibit strong antioxidant capacity due to a surplus of electrons that can be used during a free radical reaction [26,28,29].…”
Section: Amino Acid Content Of Lps <1 Kdamentioning
confidence: 99%
“…In order to analyze the antioxidant properties of TCPs against H 2 O 2 -induced HUVEC injury, CCK-8 cell viability assay was examined. As shown in Figure 4A , the cell viability assay showed that H 2 O 2 treatment could induce significant HUVEC injury compared with the control group, which confirmed that H 2 O 2 -induced oxidative injury of HUVECs is a good cell model to study the antioxidant properties of some newly founded substances ( 17 19 ). TCP pretreatments with different concentrations could significantly decrease H 2 O 2 -induced oxidative injury.…”
Section: Resultsmentioning
confidence: 58%
“…The simulation of H 2 O 2 , one of the most widely studied reactive oxygen species, or its intracellular production is responsible for the activation or deregulation of various signaling pathways, and participate in the initiation and development of cardiovascular diseases such as hypertension and atherosclerosis (15,16). Therefore, H 2 O 2 -induced oxidative injury of HUVECs is a good cell model to study the antioxidant properties of some newly found substances (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%